Cinética do consumo de oxigênio no domínio severo: comparação entre homens e mulheres saudáveis e sedentários - Azevedo, Paulo Henrique Silva Marques de (2007)
The objective of the present study was to analyse and compare the kinetics of oxygen consumption between groups during running in severe domain. Eighteen healthy and sedentary participants were separated by sex, nine men and women (25,20 ± 2,60 years; 22,10 ± 1,80 years and, 77,30 ± 12,30 kg; 58,60 ± 9,60 kg, respectively). An incremental test was realized at treadmill to determine the associated speed to VO2max (vVO2max) and running to exhaustion (Tlim) at vVO2max to determine the VO2 kinetics, with data expressed by average and standard desviation. The VO2max (3,29 ± 0,62 vs 1,90 ± 0,39 L/min) (p≤0,0001); vVO2max (14 ± 2 vs 10 (3) km.h-1) (p<0,0108); amplitude (3 ± 0,70 vs 1,80 ± 0,40 L/min) (p<0,0003) was significantly increased to men. There was not detected a statistic difference between men and women to the constant time [35,80 (22,30) s vs 36,50 (6,60) s] (p<0,2973); Tlim [271 (118) s vs 261 (73) s] (p<0,6849); Target time to achieve VO2max [142,30 (84,50) s vs 175,80 (24,60) s] (p<0,2973); %Tlim to TAVO2max [43,70 (24,40) vs 72,50 (17,70)] (p<0,1903); time maintained at VO2max (TMVO2max) [145,10 (72,50) s vs 64,20 (65,30) s] (p<0,1359), expressed values by median and interquartil amplitude. We conclude that the VO2 kinetics is similar between young and sedentary men and women, despite the biggest VO2 value demonstrated by men. The prescription value to the aerobic intervalled training do not have make off the proposed by literature for medium and high performance athletes.